Pemanfaatan Biochar Plus Terhadap Tanah Entisol Pesisir Pantai dan Tanaman Sawi Hijau (Brassica juncea L.) - Welly Herman; Wuri Prameswari; Zainal Arifin (JURNAL GALUNG TROPIKA, 2020)
The use of entisol soils can be maximized by adding organic matter. One ingredient that is able to maintain water availability and water resistance is biochar which is added to Tithonia as biochar plus. This study aims to determine the benefits of biochar plus on coastal entisol soils and mustard greens (Brassica juncea L.). The study used a Completely Randomized Design (CRD) with 6 treatments and 3 replications, namely 0% coconut shell biochar + 0% Tithonia compost (O); 100% coconut shell biochar + 0% Tithonia compost (A); 75% coconut shell biochar + 25% Tithonia Compost (B); 50% Coconut Shell Biochar + 50% Tithonia Compost (C), 25% Biochar Coconut Shell + 75% Tithonia Compost (D), 0% Biochar Coconut Shell + 100% Tithonia Compost (E). Data from observations were analyzed with variance (F test), if F count was greater than F table at 5% significance level followed by Duncan's Multiple Range Test (DMRT) at 5% significance level. The parameters observed include soil analysis which includes, pH, N-total, P-available and K-dd as well as plant observations including plant height, number of leaves and root length. The results showed that Biochar plus affected the Entisol soil and the growth of mustard plants, namely the most influential formulation was 75% coconut shell biochar + 25% Tithonia compost which was seen in the height parameters of mustard greens.